PENGEMBANGAN MINUMAN INSTAN COKELAT- KEDELAI SEBAGAI MINUMAN KESEHATAN - Rosniati Rosniati (Jurnal Industri Hasil Perkebunan, 2016)
The aim of this study was to develop the instant chocolate-soybean beverage as a health drinkformulated from fermented and non-fermented cocoa powder, sucrose, and soymilk powder (creamer). Theresearch methodology uses experimental methods and analysis. Process of instant chocolate-soybeanbeverage making refers to the process of Instant Chocolate-Ginger (Rosniati, 2011). The research usesfour formulas based on material compositions i.e. formula 1 (sucrose 55%, cocoa powder from fermentedbeans, and creamer 15%), formula 2 (sucrose 55%, cocoa powder from fermented beans 30%, and soymilkpowder 15%), formula 3 (sucrose 55%, cocoa powder from non-fermented beans 30%, and creamer15%), formula 4 (sucrose 55%, cocoa beans from non-fermented beans 30%, and soymilk powder 15%).The result shows that the formula of sucrose 55%, cocoa powder from non-fermented beans 30%, andsoymilk 15% is the best product containing 11.25% polyphenol, 8.35 fat, 45.88% total sugar, 4.17 essentialamino acid, 4.77% non-essential amino acid, 45.12 unsaturated fatty acid, and 26.42 saturated fatty acid.Keywords: baverage chocolate-soybean instant, cocoa powder, and soymilk powder